2021
DOI: 10.1109/jiot.2020.3015432
|View full text |Cite
|
Sign up to set email alerts
|

A Survey on Security and Privacy Issues in Edge-Computing-Assisted Internet of Things

Abstract: Internet of Things (IoT) is an innovative paradigm envisioned to provide massive applications that are now part of our daily lives. Millions of smart devices are deployed within complex networks to provide vibrant functionalities including communications, monitoring, and controlling of critical infrastructures. However, this massive growth of IoT devices and the corresponding huge data traffic generated at the edge of the network created additional burdens on the state-of-the-art centralized cloud computing pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
111
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 239 publications
(112 citation statements)
references
References 94 publications
0
111
0
1
Order By: Relevance
“…-All other attacks, especially attacks that targets IOT nodes (edges and things) as being constrained devices must be solved. [35] Any layer of IOT paradigm such as cloud or edge. [36] Architecture Added as a new layer between physical and network layer [37] The same as fog [37] A digital ledger that can be used to maintain continuously growing data in a secure way [38].…”
Section: Discussionmentioning
confidence: 99%
“…-All other attacks, especially attacks that targets IOT nodes (edges and things) as being constrained devices must be solved. [35] Any layer of IOT paradigm such as cloud or edge. [36] Architecture Added as a new layer between physical and network layer [37] The same as fog [37] A digital ledger that can be used to maintain continuously growing data in a secure way [38].…”
Section: Discussionmentioning
confidence: 99%
“…Orchestrator / Hypervisor hosts more vDNS to accommodate the requests that cause service disruption [69] VM Escape Attack Occurs due to the isolation failure of the hypervisor and the VNFs where the attack propagates from single VNF to the hypervisor management APIs and finally to the hypervisor. Attacker gains access to infrastructure resources while sabotaging virtual firewall functionality [69] VNF Location Shift Attack Using the migration capability of NFVI from one legal boundary to another, an attacker shifts the corresponding resources to an illegal location that bans the service, exert financial penalties while violating privacy [69] Security log troubleshooting failure Compromised VNFs generate massive amount of logs on the hypervisor and deleting the initial log entries, which makes analysis of logs an arduous task while privacy leakage risks exists Softwarized Threats [113] Software Vulnerabilities Executing arbitrary code that exploit the flaws such as buffer overflow and weak firewall policies [69] Data exfiltration / destruction Data of an infected entity or a system would be transferred or destroyed without approval [156]…”
Section: Dns Amplification Attackmentioning
confidence: 99%
“…As discussed in the previous sections, the threats and attacks analysis in IoT is scattered and none of the surveys so far, to the best knowledge of the authors, covers the threats and attacks taxonomy covering architecture, protocols, and standards of IoT with possible countermeasures using rapidly evolving ubiquitous technologies, such as BC, FC, EC, and ML, simultaneously. The threats and attacks were discussed in general without focusing on architecture and protocols [38][39][40]. Security concerns were addressed in [38] using EC and in [40] using BC.…”
Section: Scope Of the Present Survey And Contributionsmentioning
confidence: 99%
“…The threats and attacks were discussed in general without focusing on architecture and protocols [38][39][40]. Security concerns were addressed in [38] using EC and in [40] using BC. The research gaps were identified, and some open research problems were proposed in [38,40].…”
Section: Scope Of the Present Survey And Contributionsmentioning
confidence: 99%
See 1 more Smart Citation